Effects of sex ratio changes in Lampreys on ecosystem based on modeling techniques - Liu, Sitong; Tong, Ziwen; Liu, Yuhe (Transactions on Computer Science and Intelligent Systems Research, 2024)
In this paper, a number of mathematical models were established to study the effects of sex ratio changes in lampreys on this ecosystem. Logistic and Verhulst models were established to describe the population dynamics of Lampreys. Then a food web model and a niche model were construct-ed to describe the food relationships and interactions between different species. The effects of sex ratio of lampreys on ecosystem stability and species interaction were analyzed. Finally, TOPSIS evaluation model was used to evaluate the contribution of sex ratio changes in lampreys to other species. The results show that the change of sex ratio of lampreys will affect their growth rate, and then affect the balance of the whole ecosystem. The model established in this paper provides an important reference for revealing the ecological adaptation significance of the sex ratio change in lampreys.